(untitled) (World of finance, 2020)
Introduction. TThe degree of satisfaction of public interests depends on the efficiency of managing the processes of formation, distribution and use of state funds of funds. Awareness of this led to the development of scientific and methodological approaches to diagnosing the status of state finance management by both individual scientists and practitioners, as well as scientific-research institutions and organizations of national and international levels. Purpose of the paper is to investigate world and domestic scientific and methodological approaches to determining the efficiency of state finance management, which will reveal the shortcomings and gaps that affect the accuracy of the results. Results. The approaches used to assess the effectiveness of state administration and state service in general, as well as state finance management and the state budget, in particular, are characterized. The criteria used to calculate the International Civil Service Effectiveness Index are defined. The indicators of the countries of the world for this index for 2019 are analyzed. The criteria for assessing the state of public administration used by the World Bank are investigated. Such result indicators of Ukraine for 2007-2017 are analyzed. The methodology for assessing the effectiveness of public finance management (PEFA), which was tested by the World Bank with a group of partners USAID, EU, GIZ in Ukraine in 2011 and 2015, is demonstrated. The result indicators of individual criteria of management efficiency are given, such as: Open Budget Index, Global Competitiveness Index, Index of Globalization. A matrix of scientists’ views on the composition of the criteria for the effectiveness of budget management is shown. The criteria and indicators of the financial management efficiency of the state sector of the economy, which in the studied methods are not included in the composition of state finances, are determined. Conclusions. The analysis showed that the scientific and methodological approach used to evaluate the effectiveness of state finance management depends on the performers understanding of the content of efficiency, the set analytical goals, the level of analysis, sources of information, the chosen methodology. It is revealed that none of the analyzed approaches allows a comprehensive assessment of the effectiveness of state finance management.